An in-hospital physiotherapy clinic improves symptoms and absenteeism among healthcare professionals with musculoskeletal conditions - Grewal, S.; Vos, V.; Theijse, R.; Klautz, R.; Grewal, N. (Frontiers in Environmental Health, 2024)
Introduction The incidence of work-related musculoskeletal disorders has been consistently high in the healthcare sectors, with significant impact on quality of life of affected individuals and costs to health services due to absenteeism. This study assesses the effectiveness of an in-hospital physiotherapy clinic “CollegaPoli” for healthcare professionals with musculoskeletal conditions. The primary objective was to evaluate the effectiveness of the “CollegaPoli” on reduction of musculoskeletal symptoms. Secondary, readiness to return to work was studied. Methods A prospective observational study was conducted between October 2022 and June 2023. Healthcare professionals with musculoskeletal conditions resulting in sick leave were included. The effects of the “CollegaPoli” on reported symptoms and work absenteeism were evaluated. Results A total of 145 participants (84.1% female) were included in the study. Mainstream of participants reported musculoskeletal symptoms in the upper extremity (54.1%) and lower back (15.8%). Around 35% of the healthcare workers reported their symptoms to be present for 1–4 weeks, 25% since the past 7 days. The return-to-work program significantly reduced the musculoskeletal symptoms (p < 0.001) and led to an 80.3% decrease in reported absenteeism among participants. Conclusion This study supports the benefits of an in-hospital physiotherapy clinic among healthcare professionals with musculoskeletal disorders, improving symptoms and reducing absenteeism.